A New Record and Characterization of Asparagus Purple Spot Caused by Stemphylium vesicarium in Korea. Issue 1 (2nd January 2019) - Han, Joon-Hee; Shin, Jong-Hwan; Fu, Teng; Kim, Kyoung Su
Abstract: In 2017, small, elliptical, brownish purple spots on spears and ferns of asparagus were found in fields of Gangwon-do. The isolated fungal species was identified as an ascomycete Stemphylium vesicarium based on morphological characteristics and molecular phylogenic analyses including nucleotide sequences of the internal transcribed spacer (ITS), glyceraldehyde-3-phosphate dehydrogenase (GAPDH), and cytochrome b (cytb). A pathogenicity test revealed that S. vesicarium was the causal agent of purple spot disease on asparagus. The occurrence of purple spots caused by S. vesicarium on asparagus is the first report in Korea.